2020
DOI: 10.1007/s10068-020-00832-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of estimated daily intake of 3-monochloropropane-1,2-diol from soy sauce in Korea

Abstract: Soy sauces collected from the Korean market were determined for 3-monochloropropane-1,2-diol (3-MCPD) and daily intake of 3-MCPD through the consumption of soy sauce was estimated. Thirty-one samples were chosen based on a market share in 2017. The amount of 3-MCPD varied from not detected to 54.97 lg/kg with a mean value of 11.62 lg/kg. Seven soy sauces, which corresponded to 23% of the analysed samples, exceeded 20 lg/kg that is a maximum limit established by the Ministry of Food and Drug Safety in Korea. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The resultant crude product was purified by silica gel column chromatography (hexane/ethyl acetate = 1:1), yielding D-MCPD as a white solid (840 mg, 55% yield, HCl salt). The synthesized product was characterized by 1 H NMR, 13 C NMR, and LCMS. 1 H NMR and 13 C NMR spectra were recorded using a Bruker AM 400 MHz Method Validation.…”
Section: Sample Preparationmentioning
confidence: 99%
See 4 more Smart Citations
“…The resultant crude product was purified by silica gel column chromatography (hexane/ethyl acetate = 1:1), yielding D-MCPD as a white solid (840 mg, 55% yield, HCl salt). The synthesized product was characterized by 1 H NMR, 13 C NMR, and LCMS. 1 H NMR and 13 C NMR spectra were recorded using a Bruker AM 400 MHz Method Validation.…”
Section: Sample Preparationmentioning
confidence: 99%
“…It is formed notably in acid-hydrolyzed vegetable protein (acid-HVP), and it is often found in significant quantities in nonfermented soy sauces. Various studies have observed high concentrations of 3-MCPD in soy sauce, raising concerns about potential human exposure through its consumption. The International Agency for Research on Cancer (IARC) has classified 3-MCPD as a Group 2B carcinogen due to its adverse effects on kidneys and male reproductive organs and its carcinogenic potential . Considering the toxicity of 3-MCPD, the Joint FAO/WHO Expert Committee on Food Additives (JECFA) established a maximum tolerable daily intake (TDI) of 2 μg/kg body weight .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations